RELIGIUSITAS PEREMPUAN MILENIAL BERCADAR DI TENGAH FENOMENA RADIKALISME-TERORISME - Athik Hidayatul Ummah (Harmoni, 2021)
The appearance of veiled women in terrorist groups and acts of terrorism creates a negative stigma on other groups of veiled women. The trend of millennial women who are involved in acts of terror or suicide bombings and how to dress is in the pros and cons. The veil is still debated in the public. However, there are still many young women who wear the veil. This study aims to find and explain the motives, experiences and meanings of religiosity for veiled millennial women in the midst of the radicalism-terrorism phenomenon. This research method uses a phenomenological approach. The methods of data collection are interviews, observation and literature study. The subjects of this study were veiled women who were represented by a purposive sampling technique, namely based on certain criteria including: younger millennial (22-29 years old), they has used or is currently using the veil, they has read or heard studies about radicalism-terrorism, and they have negative stigma related to the use of the veil. The informants of this study found 5 people in the city of Mataram. Data obtained in the field by qualitative analysis and compared with several appropriate previous studies. The results show that the meaning of religiosity for millennial women with veils explains three dimensions, namely the intellectual dimension (religious knowledge), the experiential dimension (religious feeling), and the consequence dimension (religious effect). Meanwhile, veiled motivation comes from internal and external factors. The motivation can strengthen and change the decision to veil in the midst of the phenomenon of radicalism and terrorism. So there is no ideological dimension to the veiled decision.